2020
DOI: 10.3390/jcm9072240
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Colonization within the First Six Weeks of Life and Pulmonary Outcome in Preterm Infants <1000 g

Abstract: Bronchopulmonary dysplasia (BPD) is a multifactorial disease mainly provoked by pre- and postnatal infections, mechanical ventilation, and oxygen toxicity. In severely affected premature infants requiring mechanical ventilation, association of bacterial colonization of the lung and BPD was recently disclosed. To analyze the impact of bacterial colonization of the upper airway and gastrointestinal tract on moderate/severe BPD, we retrospectively analyzed nasopharyngeal and anal swabs taken weekly during the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 58 publications
5
16
0
Order By: Relevance
“…These actions observed for BPD animal models are in line with the main actions described for EV in general [ 102 ]. In the context of EV delivery to the immature lung, further drivers of BPD as infections and microbial dysbiosis have not been evaluated so far [ 103 , 104 ]. However, promising studies have been conducted on the treatment of neonatal sepsis [ 105 ].…”
Section: Is the Secretome The Key To Practicality And Safety Of Msmentioning
confidence: 99%
“…These actions observed for BPD animal models are in line with the main actions described for EV in general [ 102 ]. In the context of EV delivery to the immature lung, further drivers of BPD as infections and microbial dysbiosis have not been evaluated so far [ 103 , 104 ]. However, promising studies have been conducted on the treatment of neonatal sepsis [ 105 ].…”
Section: Is the Secretome The Key To Practicality And Safety Of Msmentioning
confidence: 99%
“…A further dimension that deserves more detailed clarification is the microbial colonization in utero and after birth. Clear associations have been demonstrated with the extent of lung injury, but the few preclinical studies so far do not deliver congruent results [16,17]. Therefore, this review is restricted to the available research data, mostly on isolated ROS toxicity, but important studies combining hyperoxic and infectious injury are cited where appropriate.…”
Section: The Link Between Oxygen Exposure Ros Production and Bpdmentioning
confidence: 99%
“…9 Paradoxically, however, Althouse et al 56 reported that although MAE caused gut dysbiosis, this did not dramatically exacerbate the hyperoxia lung injury phenotype. Other studies have indicated that the lung microbiota is more likely to influence BPD severity than the gut microbiota, 57 suggesting that the correlation between gut microbiota and BPD needs further investigation.…”
Section: Gut Dysbiosis and Bpdmentioning
confidence: 99%